The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1038/sj.bmt.1701062
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral blood stem cell transplantation for multiple myeloma: a report of 259 cases from the Spanish Registry

Abstract: dard chemotherapy have a median survival ranging from Among the 248 patients evaluable for response 125 24 to 36 months with less than 5% of patients surviving at (51%) had a CR and 100 had a PR (40%). The median 10 years. 1-3 The response rates to most conventional duration of progression-free survival (PFS) and overall chemotherapy regimens are usually between 40 and 60%, survival (OS) after transplantation was 23 and 35and only 5 to 10% of these responses consist of complete months, respectively. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 6 publications
(12 reference statements)
6
94
1
Order By: Relevance
“…The response rate is high and it is similar to that reported from other large studies. 20,21 The TRM (3% in our study) was also similar to the findings of other groups. 20,22,23 Advanced age has been shown to be a negative prognostic factor in some trials using ASCT for MM.…”
Section: Discussionsupporting
confidence: 80%
“…The response rate is high and it is similar to that reported from other large studies. 20,21 The TRM (3% in our study) was also similar to the findings of other groups. 20,22,23 Advanced age has been shown to be a negative prognostic factor in some trials using ASCT for MM.…”
Section: Discussionsupporting
confidence: 80%
“…Cyclophosphamide, both as parent compound and as alkylating moiety, is excreted through the kidney in percentages ranging from 1 to 14%, 19 which seems to be independent of renal function. Busulfan has been employed in preparative regimens for stem cell transplantation in MM patients; 20,21 only negligible amounts of the compound are eliminated through the kidney, as the liver is the major site of drug metabolism. 22 Concerning melphalan, data are more controversial, as several studies have suggested that pharmacokinetic parameters are related to creatinine clearance, 7,23 while other authors demonstrated that the main route of melphalan elimination is spontaneous degradation.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize mucositis, the dose of melphalan and busulfan was reduced by 20% in all protocols. Five patients with lymphoma received the BEAM regimen, 20 10 a combination of busulfan and melphalan (Bu-MPH), 21 three patients a combination of busulfan and CTX (Bu-CTX), and the one with lung cancer a combination of VP-16 and CTX. …”
Section: Myeloablative Therapiesmentioning
confidence: 99%